Development and Impact of Education for Adolescents in the Transition to Adulthood: A Systematic Literature Review - Faqihudin, Muhamad; Shobahiya, Mahasri; Taufik, T; Rifai, Alfan (Universitas Muhammadiyah Surakarta, 2025)
This study aims to explore the role of education in supporting adolescents' transition to adulthood, focusing on its impact on psychosocial development, identity formation, and emotional regulation. The approach used is a systematic literature review (SLR) with the PRISMA 2020 guidelines to ensure transparency and accuracy in data synthesis. A literature search was conducted on the Scopus database, which yielded 10 articles that met the inclusion criteria related to formal education and adolescent development. The results showed that education has a significant influence on shaping self-identity, improving emotional regulation, and preparing adolescents for mature decision-making, especially regarding careers and social responsibilities. In addition, education also improves psychological well-being, with interventions that combine social-emotional learning and experiences that enhance adolescents' emotional resilience. These findings also highlight the importance of the role of family and an inclusive educational environment in supporting adolescent development. Based on these findings, it is recommended that education policies place greater emphasis on psychosocial aspects rather than just academics, by creating an educational environment that supports the development of adolescents' identity, autonomy, and emotional well-being. Education that focuses on social-emotional development can accelerate adolescents' transition to healthier and more responsible adulthood.